علم الجمال - المفهوم والقيمة والاتجاهات الجمالية - الجاني, عبد الباسط (Sharwes Scientific Journal, 2023)
This research means studying the aesthetic concept and aesthetic value by reviewing the most important things that philosophers and theorists have dealt with their various literary and intellectual references.The research included a presentation of the research problem, which can be summarized by answering the following question:What is the relationship between the aesthetic concept and aesthetic value through artistic definitions of beauty and its value standard?The aim of the research is to reveal the criterion for the aesthetic value of these aesthetic theories and opinions in philosophical thought. Results including:1- Harmony: It is represented by the value of the product provided and the parts that are compatible with the availability of other parts. It is also considered to be the union of the various elements that make up the object or thing.2- Perfection: which gives value to what is considered free of defects or errors. The word perfection may come from the word “perfection,” which means something that is complete, completely finished, and has reached the highest level available.3- Balance: This value is considered to be the one that deals with the artistic situation when each component part of it exerts the effect that it produces the other parts are then replaced and canceled at the same time, which in turn indicates stability.4- Seriousness: Seriousness refers to a high degree of seriousness and formality so that all harsh and heavy feelings come out of the artwork without losing its impression-generating quality.5- Delicacy: A value associated with the characteristics of delicacy, softness, splendor, and attractiveness, which is in contrast to strength and roughness. Sensitivity is sometimes associated with both fragility or care and detail that a work of art may cause.It also includes an index of research sources.